Preparation method of carboxymethyl cellulose / montmorillonite biomass mulching film material in magnetic field environment
By loading montmorillonite with magnetic particles in a magnetic field environment and organically modifying, combining carboxymethyl cellulose, and arranging montmorillonite through a magnetic field, biomass plastic film materials with excellent barrier properties were prepared, which solved the problems of non-biodegradation of traditional mulch films and insufficient biomass plastic film performance, and achieved high-performance and environmentally friendly agricultural mulch materials.
Patent Information
- Application Number
- CN202510141950.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-09
- Publication Date
- 2025-05-02
AI Technical Summary
Traditional plastic plastic films are not biodegradable, resulting in white pollution, while biomass plastic films are difficult to widely use in agricultural production due to insufficient interface adhesion, water vapor barrier properties and mechanical properties.
In a magnetic field environment, montmorillonite is loaded with magnetic particles and organically modified, combined with carboxymethyl cellulose, and arranged montmorillonite in a directional manner through a magnetic field device to prepare a biomass plastic film material with excellent barrier properties.
The prepared biomass plastic film materials have good UV resistance, water vapor permeability, biodegradability and mechanical strength, which can effectively reduce the damage of UV to crops and avoid soil pollution by traditional plastic films.
Abstract
Description
Technical Field
[0001] The invention relates to an agricultural ground film, in particular to a method for preparing a carboxymethyl cellulose / montmorillonite biofilm material in a magnetic field environment, which is suitable for ground covering films with barrier function requirements in agriculture and belongs to the field of agricultural and forestry chemical materials. Background Art
[0002] With the global population growth and the continuous rise in food demand, mulching technology has been widely used because of its advantages such as maintaining soil moisture and temperature, promoting crop growth, and increasing yields. Although traditional plastic mulch has excellent barrier properties, its non-biodegradable nature leads to the accumulation of a large amount of residues, causing white pollution, and seriously threatening the ecological environment and human health. In contrast, biofilm has environmental advantages, but due to its limited interfacial adhesion, poor water vapor barrier, insufficient water resistance, and mechanical properties far inferior to plastic mulch, it is difficult to be widely used in actual agricultural production. Therefore, improving the barrier properties of biofilm and using it as a substitute for plastic mulch is of great significance to promoting the green and sustainable development of agriculture.
[0003] Carboxymethyl cellulose is an anionic, water-soluble, non-toxic natural polysaccharide. It is commonly used in pharmaceutical, cosmetic, food industry and water purification fields due to its good film-forming ability, excellent water absorption performance and abundant hydrophilic carboxyl groups. However, the film prepared from pure carboxymethyl cellulose has poor barrier properties and general thermal stability, which limits the practical application of carboxymethyl cellulose film.
[0004] Montmorillonite is a material with abundant mineral resources, low cost and wide application. It is widely used in light industry, metallurgy, oil refining, wastewater treatment and other industries. Its crystal structure consists of a layer of aluminum oxide octahedron and two layers of silicon oxide tetrahedron, forming a 2:1 sandwich structure. The interlayer force of montmorillonite is weak, and water molecules can easily penetrate and cause expansion, resulting in an increase in the interlayer spacing. It has a high surface area and excellent aspect ratio, so it becomes an effective additive to enhance the barrier properties of polymers.
[0005] In polymer composites, the distribution state and orientation of fillers have a significant impact on their barrier properties. Since nano-montmorillonite flakes tend to be randomly arranged in the polymer matrix under thermal energy disturbance and present a disordered distribution, an external energy field is required to achieve their orderly arrangement. As a non-contact physical field, the size and direction of the magnetic field can be flexibly adjusted and is suitable for particles of different shapes and sizes. By regulating the directional arrangement of montmorillonite by applying an external magnetic field, a biofilm with excellent barrier properties, outstanding functions and environmental friendliness can be prepared. Summary of the invention
[0006] The present invention provides a method for preparing a carboxymethyl cellulose / montmorillonite biomass film material in a magnetic field environment, wherein the montmorillonite is loaded with magnetic particles and organically modified, and then the montmorillonite suspension and the carboxymethyl cellulose solution are mixed in a certain proportion to form a film-forming liquid, and the montmorillonite in the film-forming liquid is oriented and arranged by a magnetic field device, and the biomass film material with excellent barrier properties such as blocking ultraviolet rays and blocking water vapor is obtained after drying.
[0007] To achieve the above purpose, the carboxymethyl cellulose / montmorillonite biofilm material prepared in the magnetic field environment has a thickness of 70-150 μm, a tensile load strength of 6-29 MPa in a dry state, an elongation at break of 10-64%, an ultraviolet blocking rate of 74%-95%, and a water vapor permeability of 900-1200 g / (m 2 ·24h).
[0008] The technical scheme adopted by the present invention is: a carboxymethyl cellulose / montmorillonite biomass ground membrane material in a magnetic field environment, firstly, ferroferric oxide is loaded on montmorillonite by a chemical precipitation method and the binding force between the two is enhanced by a silane coupling agent, then an organic modified magnetized montmorillonite is obtained by an octadecyltrimethylammonium bromide intercalation reaction, then the organic modified magnetized montmorillonite suspension and the carboxymethyl cellulose solution are mixed in a certain proportion to form a membrane-forming liquid, and the montmorillonite in the membrane-forming liquid is subjected to a directional arrangement treatment by a magnetic field device, and then after drying, a biomass ground membrane material with excellent barrier properties such as blocking ultraviolet rays and blocking water vapor is obtained.
[0009] The carboxymethyl cellulose is a carboxymethylated cellulose derivative with a relative molecular weight of 250,000 to 800,000 and a substitution degree of 0.4 to 1.2.
[0010] The montmorillonite is a sodium-based silicate with a particle size of less than 20 μm and a purity of more than 98%.
[0011] The silane coupling agent is one of 3-aminopropyltriethoxysilane and N-β-aminoethyl-γ-aminopropyltrimethoxysilane.
[0012] The external magnetic field is a rotating magnetic field device composed of two permanent magnets, and the magnetic field strength is adjustable in the range of 0mT to 100mT.
[0013] The above-mentioned method for preparing a carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment comprises the following steps: (1) Montmorillonite loaded with ferrous oxide: Montmorillonite was dispersed in water and ultrasonically treated to obtain a montmorillonite suspension. Ferric chloride hexahydrate and ferrous chloride tetrahydrate (molar ratio of 2:1) were dissolved in water respectively and mixed with the montmorillonite suspension under a nitrogen atmosphere. The mixed solution was vigorously stirred at 60-70°C, and the pH value was adjusted to 10-12 with a 28% ammonia solution; the ultrasonic treatment time was 0.5-1.5h, the mass percentage of montmorillonite in the mixed solution was 1-2%, and the total mass percentage of ferric chloride hexahydrate and ferrous chloride tetrahydrate was 3.194%-6.388%; after adding silane coupling agent to the mixed solution and continuing stirring for 2-3h, it was allowed to stand, magnetically separated, washed and vacuum dried; the mass percentage of silane coupling agent was 0.4%-0.8%, and the vacuum drying temperature was 20-40°C; (2) Preparation of organic magnetic montmorillonite: Dry the magnetic montmorillonite obtained in step (1), dissolve it in water, stir it magnetically for 12 hours, and then disperse it ultrasonically for 0.5-1.5 hours. Add octadecyltrimethylammonium bromide and ultrasonicate it for 0.5 hours, then stir it thoroughly for 2-3 hours at 80-90°C. Continue stirring until room temperature, and ultrasonicate it again for 0.5-1.5 hours. Centrifuge, wash (until 0.1 mol / L AgNO3 is added to the filtrate without precipitation), and vacuum dry to obtain organic magnetic montmorillonite; the mass ratio of magnetic montmorillonite to octadecyltrimethylammonium bromide is 3:1-5:1, and the vacuum drying temperature is 20-40°C; (3) Preparation of ground film: The organic magnetized montmorillonite obtained in step (2) is dispersed in water, stirred and ultrasonically degassed to form an organic magnetized montmorillonite suspension. Carboxymethyl cellulose and propylene glycol are added to the suspension, heated and stirred at 80-90°C to obtain a mixed film-forming liquid, and the film-forming liquid is transferred into a polytetrafluoroethylene mold and placed in a rotating magnetic field device with different field strengths to dry and form a film; the mass percentage of each component in the film-forming liquid is 0.2%-1.0% of organic magnetized montmorillonite, 1.0%-3.0% of carboxymethyl cellulose, and 0.4%-1.2% of propylene glycol, and the magnetic field strength is 15mT-60mT.
[0014] The beneficial effects of the present invention are: carboxymethyl cellulose is combined with montmorillonite loaded with magnetic particles and modified, and the montmorillonite in the film-forming liquid is oriented and arranged by a magnetic field device, so as to prepare a biofilm material with good anti-ultraviolet performance, water vapor permeability resistance, biodegradability and mechanical strength. The biofilm material can effectively reduce the damage of ultraviolet rays to crops and has good moisturizing function, while avoiding the pollution of soil by traditional plastic films, and is conducive to the green and sustainable development of agricultural films. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and beneficial technical effects of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments.
[0016] Example 1 Preparation of carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment Step 1: Montmorillonite loaded with ferrous oxide. Montmorillonite was dispersed in water and ultrasonically treated to obtain a montmorillonite suspension. Ferric chloride hexahydrate and ferrous chloride tetrahydrate (molar ratio of 2:1) were dissolved in water respectively and mixed with the montmorillonite suspension under a nitrogen atmosphere. The mixed solution was vigorously stirred at 60°C, and the pH value was adjusted to 10 with a 28% ammonia solution; the ultrasonic treatment time was 0.5h, the mass percentage of montmorillonite in the mixed solution was 1%, and the total mass percentage of ferric chloride hexahydrate and ferrous chloride tetrahydrate was 3.194%; after adding silane coupling agent to the mixed solution and continuing stirring for 2h, it was allowed to stand, magnetically separated, washed and vacuum dried; the mass percentage of silane coupling agent was 0.4%, and the vacuum drying temperature was 20°C; Step 2: Preparation of organic magnetic montmorillonite. The magnetic montmorillonite obtained in the first step is dried, dissolved in water, magnetically stirred for 12 hours, and then ultrasonically dispersed for 0.5 hours. After adding octadecyltrimethylammonium bromide and ultrasonicating for 0.5 hours, it is fully stirred at 80°C for another 2 hours. Stirring is continued until room temperature, and ultrasonicating is performed again for 0.5 hours. After centrifugation, washing (until 0.1 mol / LAgNO3 is added to the filtrate without precipitation), and vacuum drying, organic magnetic montmorillonite is obtained; the mass ratio of magnetic montmorillonite to octadecyltrimethylammonium bromide is 3:1, and the vacuum drying temperature is 20°C; Step 3: Preparation of ground film. The organic magnetized montmorillonite obtained in the second step is dispersed in water, stirred and ultrasonically degassed to form an organic magnetized montmorillonite suspension. Carboxymethyl cellulose and glycerol are added to the suspension, heated and stirred at 80°C to obtain a mixed film-forming liquid, which is transferred into a polytetrafluoroethylene mold and placed in a rotating magnetic field device with different field strengths to dry and form a film; the mass percentage of each component in the film-forming liquid is 0.2% organic magnetized montmorillonite, 1.0% carboxymethyl cellulose, and 0.4% glycerol, and the magnetic field strength is 15mT.
[0017] Example 2 Preparation of carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment Step 1: Montmorillonite loaded with ferrous oxide. Montmorillonite was dispersed in water and ultrasonically treated to obtain a montmorillonite suspension. Ferric chloride hexahydrate and ferrous chloride tetrahydrate (molar ratio of 2:1) were dissolved in water respectively and mixed with the montmorillonite suspension under a nitrogen atmosphere. The mixed solution was vigorously stirred at 65°C, and the pH value was adjusted to 11 with a 28% ammonia solution; the ultrasonic treatment time was 1h, and the mass percentage of montmorillonite in the mixed solution was 1.5%, and the total mass percentage of ferric chloride hexahydrate and ferrous chloride tetrahydrate was 4.791%; after adding silane coupling agent to the mixed solution and continuing to stir for 2.5h, it was allowed to stand, magnetically separated, washed and vacuum dried; the mass percentage of silane coupling agent was 0.6%, and the vacuum drying temperature was 30°C; Step 2: Preparation of organic magnetic montmorillonite. The magnetic montmorillonite obtained in the first step is dried, dissolved in water, and magnetically stirred for 12 hours and then ultrasonically dispersed for 1 hour; octadecyltrimethylammonium bromide is added and ultrasonicated for 0.5 hours, and then fully stirred at 85°C for 2.5 hours. Stirring is continued until room temperature, and ultrasonicated again for 1 hour, and organic magnetic montmorillonite is obtained after centrifugation, washing (until 0.1 mol / LAgNO3 is added to the filtrate without precipitation), and vacuum drying; the mass ratio of magnetic montmorillonite to octadecyltrimethylammonium bromide is 4:1, and the vacuum drying temperature is 30°C; Step 3: Preparation of ground film. The organic magnetized montmorillonite obtained in the second step is dispersed in water, stirred and ultrasonically degassed to form an organic magnetized montmorillonite suspension. Carboxymethyl cellulose and glycerol are added to the suspension, heated and stirred at 85°C to obtain a mixed film-forming liquid, which is transferred into a polytetrafluoroethylene mold and placed in a rotating magnetic field device with different field strengths to dry and form a film; the mass percentage of each component in the film-forming liquid is 0.6% organic magnetized montmorillonite, 2.0% carboxymethyl cellulose, and 0.8% glycerol, and the magnetic field strength is 40mT.
[0018] Example 3 Preparation of carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment Step 1: Montmorillonite loaded with ferrous oxide. Montmorillonite was dispersed in water and ultrasonically treated to obtain a montmorillonite suspension. Ferric chloride hexahydrate and ferrous chloride tetrahydrate (molar ratio of 2:1) were dissolved in water respectively and mixed with the montmorillonite suspension under a nitrogen atmosphere. The mixed solution was vigorously stirred at 70°C, and the pH value was adjusted to 12 with a 28% ammonia solution; the ultrasonic treatment time was 1.5h, the mass percentage of montmorillonite in the mixed solution was 2%, and the total mass percentage of ferric chloride hexahydrate and ferrous chloride tetrahydrate was 6.388%; after adding silane coupling agent to the mixed solution and continuing stirring for 3h, it was allowed to stand, magnetically separated, washed and vacuum dried; the mass percentage of silane coupling agent was 0.8%, and the vacuum drying temperature was 40°C; Step 2: Preparation of organic magnetic montmorillonite. The magnetic montmorillonite obtained in the first step is dried, dissolved in water, magnetically stirred for 12 hours, and then ultrasonically dispersed for 1.5 hours. After adding octadecyltrimethylammonium bromide and ultrasonicating for 0.5 hours, it is fully stirred at 90°C for another 3 hours. Stirring is continued until room temperature, and ultrasonicating is performed again for 1.5 hours. After centrifugation, washing (until 0.1 mol / L AgNO3 is added to the filtrate without precipitation), and vacuum drying, organic magnetic montmorillonite is obtained; the mass ratio of magnetic montmorillonite to octadecyltrimethylammonium bromide is 5:1, and the vacuum drying temperature is 40°C; Step 3: Preparation of ground film. The organic magnetized montmorillonite obtained in the second step is dispersed in water, stirred and ultrasonically degassed to form an organic magnetized montmorillonite suspension. Carboxymethyl cellulose and glycerol are added to the suspension, heated and stirred at 90°C to obtain a mixed film-forming liquid, which is transferred into a polytetrafluoroethylene mold and placed in a rotating magnetic field device with different field strengths to dry and form a film; the mass percentage of each component in the film-forming liquid is 1.0% organic magnetized montmorillonite, 3.0% carboxymethyl cellulose, and 1.2% glycerol, and the magnetic field strength is 60mT.
[0019] The carboxymethyl cellulose / montmorillonite biofilm materials produced in the magnetic field environment of Examples 1-3 were tested: the film thickness was 70-150 μm, the tensile load strength was 6-29 MPa, the elongation at break was 10-64%, the UV blocking rate was 74%-95%, and the water vapor permeability was 900-1200 g / (m 2 ·24h). It can be seen that the ground film material produced by the present invention not only has good mechanical properties, but also has good ultraviolet and water vapor blocking capabilities.
[0020] The above description points out and describes several preferred embodiments of the present invention, but it should be understood that the present invention is not limited to the form disclosed herein and should not be regarded as excluding other embodiments. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment, characterized in that: Ferroferric oxide is loaded on montmorillonite by chemical precipitation method and the binding force between the two is enhanced by silane coupling agent, then organic modified magnetized montmorillonite is obtained by octadecyltrimethylammonium bromide intercalation reaction, then the organic modified magnetized montmorillonite suspension is mixed with carboxymethyl cellulose solution in a certain proportion to form a film-forming liquid, and the montmorillonite in the film-forming liquid is oriented and arranged by a magnetic field device, and then dried to obtain a biomass ground membrane material with excellent barrier properties such as blocking ultraviolet rays and blocking water vapor.
2. The carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment according to claim 1, characterized in that: The film has a thickness of 70-150 μm, a tensile load strength of 6-29 MPa in a dry state, an elongation at break of 10-64%, an ultraviolet blocking rate of 74%-95%, and a water vapor permeability of 900-1200 g / (m 2 ·24h).
3. The carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment according to claim 1, characterized in that: The carboxymethyl cellulose is a carboxymethylated cellulose derivative with a relative molecular weight of 250,000 to 800,000 and a degree of substitution of 0.4 to 1.
2.
4. The carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment according to claim 1, characterized in that: The montmorillonite is a sodium-based silicate with a particle size of less than 20 μm and a purity of more than 98%.
5. The carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment according to claim 1, characterized in that: The silane coupling agent is one of 3-aminopropyltriethoxysilane and N-β-aminoethyl-γ-aminopropyltrimethoxysilane.
6. The carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment according to claim 1, characterized in that: The external magnetic field is a rotating magnetic field device composed of two permanent magnets, and the magnetic field intensity is adjustable in the range of 0mT to 100mT.
7. A method for preparing a carboxymethyl cellulose / montmorillonite biomass membrane material in a magnetic field environment as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Montmorillonite loaded with ferrous oxide: Montmorillonite was dispersed in water and ultrasonically treated to obtain a montmorillonite suspension. Ferric chloride hexahydrate and ferrous chloride tetrahydrate (molar ratio of 2:1) were dissolved in water respectively and mixed with the montmorillonite suspension under a nitrogen atmosphere. The mixed solution was vigorously stirred at 60-70°C, and the pH value was adjusted to 10-12 with a 28% ammonia solution; the ultrasonic treatment time was 0.5-1.5h, the mass percentage of montmorillonite in the mixed solution was 1-2%, and the total mass percentage of ferric chloride hexahydrate and ferrous chloride tetrahydrate was 3.194%-6.388%; after adding silane coupling agent to the mixed solution and continuing stirring for 2-3h, it was allowed to stand, magnetically separated, washed and vacuum dried; the mass percentage of silane coupling agent was 0.4%-0.8%, and the vacuum drying temperature was 20-40°C; (2) Preparation of organic magnetic montmorillonite: Dry the magnetic montmorillonite obtained in step (1), dissolve it in water, stir it magnetically for 12 hours, and then disperse it ultrasonically for 0.5-1.5 hours. Add octadecyltrimethylammonium bromide and ultrasonicate it for 0.5 hours, then stir it thoroughly for 2-3 hours at 80-90°C. Continue stirring until room temperature, and ultrasonicate it again for 0.5-1.5 hours. Centrifuge, wash (until 0.1 mol / L AgNO3 is added to the filtrate without precipitation), and vacuum dry to obtain organic magnetic montmorillonite; the mass ratio of magnetic montmorillonite to octadecyltrimethylammonium bromide is 3:1-5:1, and the vacuum drying temperature is 20-40°C; (3) Preparation of ground film: The organic magnetized montmorillonite obtained in step (2) is dispersed in water, stirred and ultrasonically degassed to form an organic magnetized montmorillonite suspension. Carboxymethyl cellulose and propylene glycol are added to the suspension, heated and stirred at 80-90°C to obtain a mixed film-forming liquid, and the film-forming liquid is transferred into a polytetrafluoroethylene mold and placed in a rotating magnetic field device with different field strengths to dry and form a film; the mass percentage of each component in the film-forming liquid is 0.2%-1.0% of organic magnetized montmorillonite, 1.0%-3.0% of carboxymethyl cellulose, and 0.4%-1.2% of propylene glycol, and the magnetic field strength is 15mT-60mT.
Citation Information
Cited By
Preparation method of food plastic packaging bag
CN121699253A